Pembagian Harta Bersama dalam Perceraian Ditinjau dari Perspektif Teori Keadilan - Salsabila, Shafa (Zaaken: Journal of Civil and Business Law, 2023)
This thesis examines the Division of Joint Property in Divorce from the Perspective of Justice Theory using 2 court decisions, namely the Banjarmasin Religious Court and the Banten High Religious Court. Based on Law Number 1 of 1974 concerning Marriage, the Compilation of Islam Law, and the Decision of Religious Court Judges. This study aims to determine the legal consequences arising from the judge's consideration in determining the case of division of joint property and analyze the judge's consideration in determining the case of division of joint property based on the theory of justice according to Aristotle and Islamic Law. Formulation of the problem: (1) What are the legal consequences for the judge's consideration in decision Number 1227/Pdt.G/2021/PA. Bjm and decision Number 91/Pdt.G/2021/ PTA.Btn? (2) How is the analysis of the judge's consideration in the division of joint property in decision Number 1227/Pdt.G/2021/PA. Bjm and decision Number 91/Pdt.G/2021/PTA.Btn in the perspective of the theory of justice? This study used normative juridical legal methods. Regarding joint property in marriage, many people ignore it, so there is often an uproar after the judge decides on the divorce between husband and wife. In Article 97 of the Compilation of Islamic Law "The widow or widower gets half of the joint property", but in the decision of the Religious Court Number 1227/Pdt.G/2021/PA. Bjm and Number 91/Pdt.G/2021/PTA.Btn, the panel of judges set aside the article by not dividing the joint property equally. So that article 97 of the Compilation of Islamic Law is less effective in resolving cases of division of common property which causes blurring of norms and requires judges to make decisions based on their beliefs. And the judge's consideration in deciding cases is included in the theory of distributive justice by dividing the object of common property according to what he has done so that it reflects the value of justice.    Abstrak Skripsi ini mengkaji tentang Pembagian Harta Bersama Dalam Perceraian Ditinjau dari Perspektif Teori Keadilan dengan menggunakan 2 putusan pengadilan yaitu Pengadilan Agama Banjarmasin dan Pengadilan Agama Tinggi Banten. Berlandaskan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan, Kompilasi Hukum Islam, dan Putusan Hakim Pengadilan Agama. Penelitian ini bertujuan untuk mengetahui akibat hukum yang ditimbulkan dari pertimbangan hakim dalam menetapkan perkara pembagian harta bersama dan menganalisis pertimbangan hakim dalam menetapkan perkara pembagian harta bersama berdasarkan teori keadilan menurut Aristoteles dan Hukum Islam. Rumusan masalah : (1) Bagaimana akibat hukum atas pertimbangan hakim dalam putusan Nomor 1227/Pdt.G/2021/PA. Bjm dan putusan Nomor 91/Pdt.G/2021/PTA. Btn? (2) Bagaimana analisis pertimbangan hakim dalam pembagian harta bersama pada putusan Nomor 1227/Pdt.G/2021/PA. Bjm dan putusan Nomor 91/Pdt.G/2021/PTA. Btn dalam perspektif teori keadilan?. Penelitian ini menggunakan metode hukum yuridis normatif. Terkait harta bersama dalam perkawinan banyak masyarakat yang mengabaikannya sehingga sering terjadi keributan setelah hakim memutuskan perceraian antara suami dan isteri. Dalam Pasal 97 Kompilasi Hukum Islam "Janda atau duda mendapat separuh dari harta bersama", namun pada putusan Pengadilan Agama Nomor 1227/Pdt.G/2021/PA. Bjm dan Nomor 91/Pdt.G/2021/PTA. Btn, majelis hakim mengeyampingkan pasal tersebut dengan tidak membagi rata harta bersama. Sehingga dalam pasal 97 Kompilasi Hukum Islam kurang efektif dalam menyelesaikan perkara pembagian harta bersama yang menyebabkan terjadinya kekaburan norma dan mengharuskan hakim untuk mengambil keputusan berdasarkan keyakinan yang dimiliki. Dan pertimbangan hakim dalam memutuskan perkara termasuk ke dalam teori keadilan distributif dengan membagi obyek harta bersama sesuai dengan apa yang telah dilakukannya sehingga sudah mencerminkan nilai keadilan.